73 GASTRIC ELECTRICAL STIMULATION AND SACRAL ELECTRICAL STIMULATION: ARE TWO DEVICES BETTER THAN ONE?. (1st January 2006) - Jain, S.; Al-Juburi, A.; Brizzolora, J.; Secrest, C. L.; Abell, T. L.
Abstract : Introduction: Gastric electrical stimulation (GES) is available as a humanitarian use device for patients with the symptoms of gastroparesis and is effective in reducing gastrointestinal symptoms. We have previously shown that patients with gastric motor disorders often have coexisting abnormalities of the genitourinary system (Gastroenterology 1997;112:A737), which may now be treated with sacral electrical stimulation (SES), resulting in similar improvements in genitourinary symptoms. Patients: We compared the results of therapy with GES and SES in 13 patients who were implanted with both devices. Patients were 11 F, 2 M, mean age of 41 years, who had documented gastroparesis as well as bladder or other pelvic floor dysfunction. All 13 patients had received their GES before the SES. Methods: Patients were evaluated at baseline and latest follow-up (median 4 years for GES and 2 years for SES), according to previously standardized scores of GI (GI: 0-4, TSS max 20) and GU (GU: 0-3, UTSS, max 12) function. Results were compared by paired t-tests and reported as mean 6 SE. Results: All 13 patients improved both GI and GU symptoms and the improvement in all parameters as nausea, vomiting, anorexia, bloating, abdominal pain and gastric total symptom score (TSS), leakage, urgency, voiding difficulty, number of pads used, and urinary total symptom score (UTSS) was statistically significant (see table below). Conclusions: The combination of GES and SES appears to be both safe and effective for patients with concomitant gastroparesis and bladder dysfunction and the existence of a one stimulator does not preclude another.